(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The article discusses the role of the Jadids in the development of the Uzbek literary language, their views on the new alphabet, and their services in this field. In particular, initiatives to introduce a new alphabet will be analyzed. The results and importance of these events are shown.